2019
DOI: 10.3390/molecules24081640
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Kabachnik–Fields Reaction with Amino Alcohols as the Amine Component

Abstract: In this paper, the microwave (MW)-assisted catalyst-free and mostly solvent-free Kabachnik–Fields reaction of amino alcohols, paraformaldehyde, and various >P(O)H reagents (dialkyl phosphites, ethyl phenyl-H-phosphinate, and secondary phosphine oxides) is reported. The synthesis of N-2-hydroxyethyl-αaminophosphonate derivatives was optimized in respect of the temperature, the reaction time, and the molar ratio of the starting materials. A few by-products were also identified. N,NBis(phosphinoylmethyl)amines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…[ 112 ] The carbonyl group is bonded with an amine to form imine, followed by the PH bond on the homophosphate molecule by double bond addition (Pudovik reaction) to form amino phosphonate, which is executed under mild environmental system and water is the only by‐product. [ 113,114 ] KF reaction can be employed for two polymer linkage and polycondensation or end chain functionalization. In addition, surface functionalization of inorganic substrate materials can also be accomplished by a one‐step KF reaction.…”
Section: Fabrication Of Fluorescent Copolymers With Aie Feature Throumentioning
confidence: 99%
“…[ 112 ] The carbonyl group is bonded with an amine to form imine, followed by the PH bond on the homophosphate molecule by double bond addition (Pudovik reaction) to form amino phosphonate, which is executed under mild environmental system and water is the only by‐product. [ 113,114 ] KF reaction can be employed for two polymer linkage and polycondensation or end chain functionalization. In addition, surface functionalization of inorganic substrate materials can also be accomplished by a one‐step KF reaction.…”
Section: Fabrication Of Fluorescent Copolymers With Aie Feature Throumentioning
confidence: 99%
“…In this context, Kabachnic and co-workers in 2005 successfully established the possibility of incorporating α-aminophosphonate into natural porphyrins through KF reaction, where condensation of natural porphyrins with tert-butyl amine and diethylphosphite (1 : 1 : 3) in DCM was accomplished in good to excellent yields by irradiating with MW radiations (Scheme 52). 51 Clercq et al in one of their previous works, reported a synthetic strategy for obtaining quinoline-based α-aminophoshphonates.52 However, the desired product was furnished in poor yield (< 20 %). In 2009, Juribasic and Tusek-bozic have successfully employed MW radiations in a three-component one pot reaction between quinoline-3-carboxaldehyde and aniline as well as 3-aminoquinoline and benzaldehyde with diethylphosphite.…”
Section: A N-heterocyclesmentioning
confidence: 99%
“…Additionally, a single crystal of cyclohexadiene product 4a was also prepared; however, in contrast to the high-pressure conditions appropriate for the preparation of 3, here thermal activation with microwaves was necessary. Microwave irradiation as a way to facilitate organic reactions has during the last decades found some surprisingly widespread applications, as recently vividly described by Kappe [48], including acceleration of Diels-Alder reactions [2,49], Kabachnik-Fields reaction [50] and many others. It is worth noting that product endo-3e was isolated by precipitation upon slow evaporation of the volatile components from the mother liquor (which remained after the precipitation of exo-3e and its removal by vacuum filtration) containing an appreciable amount of the starting dienophile 6a (which was initially applied in a large excess, also as a co-solvent, in molar ratio 1e:6a = 1:27).…”
Section: Chemistrymentioning
confidence: 99%